Warped Product Lightlike Submanifolds - Şahin, Bayram (Sarajevo Journal of Mathematics, 2024)
e study a new class of lightlike submanifolds M, called warped product lightlike submanifolds, of a semi-Riemann manifold. We show that the null geometry of M reduces to the corresponding non-degenerate geometry of its semi-Riemann submanifold. 2000 Mathematics Subject Classification. 53C15, 53C40, 53C50